Single agent daratumumab in advanced multiple myeloma possesses significant efficacy even in an unselected "real-world" population - Minarik, Jiri; Pour, Ludek; Maisnar, Vladimir; Spicka, Ivan; Jungova, Alexandra; Jelinek, Tomas; Brozova, Lucie; Krhovska, Petra; Scudla, Vlastimil; Hajek, Roman (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2019)
OBJECTIVE: The treatment of relapsed and refractory multiple myeloma (RRMM) remains challenging. The outcomes in highly pretreated populations are unsatisfactory and there is urgent need for novel and safe therapeutic approaches. Recently, daratumumab has been approved for RRMM with promising results even in monotherapy. The aim of this study was to assess the efficacy of single agent daratumumab outside a clinical trial. PATIENTS AND METHODS: 14 patients with RRMM and significant pretreatment (median 4.5 previous lines) entered a specific healthcare program and received treatment with single agent daratumumab. They were followed for therapeutic response based on IMWG criteria, and incidence of adverse events. The data were collected using the Registry of Monoclonal Gammopathies. RESULTS: The overall response rate was 38.5%. 23.1% of patients reached very good partial response, 15.4% reached partial remission, 15.4% had minimal response, 38.5% had stable disease and 7.7% had progressive disease. The median progression free survival was 4.6 months and median overall survival was not achieved. The toxicities were mostly mild, only infectious complications and hematological toxicity reached grade III. CONCLUSION: We conclude that daratumumab has significant activity in highly pretreated RRMM even as a single agent, with an acceptable toxicity profile and survival impact.
Keywords: výsledek terapie; Recurrence; relapsed and refractory; Disease-Free Survival; Male; monoklonální protilátky; overall survival; protinádorové látky; lokální recidiva nádoru; multiple myeloma; Adult; Aged; dospělí; Multiple Myeloma; mužské pohlaví; senioři; recidiva; Treatment Outcome; progression free survival; Neoplasm Recurrence, Local; senioři nad 80 let; lidé; ženské pohlaví; Humans; daratumumab; Aged, 80 and over; Antibodies, Monoclonal; mnohočetný myelom; Female; lidé středního věku; přežití bez známek nemoci; Antineoplastic Agents; Middle Aged